Psychodynamic neurology : dreams, consciousness, and virtual reality - Hobson, J. Allan, 1933- (Boca Raton : CRC Press/Taylor & Francis Group, 2015)
'Our brains plan conscious experience in our sleep using our waking experience only to correct a built-in, virtual reality model of the world that becomes more fully active when we sleep. We become subjectively aware of that virtual reality model when we dream. Our dreams are a mixture of anticipated virtual and remembered real experience. This book tells the story of now neuroscience has helped us reach this startling and exciting conclusion and how the new scientific model builds upon and also departs from the dream theories of the past. It recounts how modern sleep and dream science developed from its inception in 1953 with the discovery of REM sleep and its association with dreaming. It explains how initial enthusiasm for Freud's dream theory waned and ultimately gave way to the alternative ideas described in detail throughout this book'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Dreams -- Physiology; Brain -- Physiology; Consciousness -- physiology; Mental Processes -- physiology; Neuropsychology; Sleep -- Physiology